2023
DOI: 10.1002/eat.24028
|View full text |Cite
|
Sign up to set email alerts
|

Emotional food‐cue‐reactivity in anorexia nervosa and bulimia nervosa: An electroencephalography study

Abstract: ObjectiveFood‐cue‐reactivity entails neural and experiential responses to the sight and smell of attractive foods. Negative emotions can modulate such cue‐reactivity and this might be central to the balance between restrictive versus bulimic symptomatology in Anorexia Nervosa (AN) and Bulimia Nervosa (BN).MethodPleasantness ratings and electrocortical responses to food images were measured in patients with AN (n = 35), BN (n = 32) and matched healthy controls (HC, n = 35) in a neutral state and after idiosyncr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Changes in EEG, which is used in the diagnosis and follow-up of various neurological diseases, have also been investigated in eating disorders [10]. Some cortical dysfunctions were detected in EEG studies performed in patients with anorexia nervosa [11,12]. Some of these studies reported that cortical dysfunctions persisted even after weight gain in patients with anorexia nervosa, while others reported normalization of EEG in patients with refeeding in anorexia nervosa [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in EEG, which is used in the diagnosis and follow-up of various neurological diseases, have also been investigated in eating disorders [10]. Some cortical dysfunctions were detected in EEG studies performed in patients with anorexia nervosa [11,12]. Some of these studies reported that cortical dysfunctions persisted even after weight gain in patients with anorexia nervosa, while others reported normalization of EEG in patients with refeeding in anorexia nervosa [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] Electrode placement in electroencephalogram.▶Table Demographic characteristics of the HEG and control groups.…”
mentioning
confidence: 99%